Teddy Roosevelt : young rough rider - Parks, Edd Winfield (New York : Aladdin Paperbacks, 1986)
Summary: Focuses on the childhood of the dynamic president, describing how Teddy worked hard to improve his poor health & developed a lifelong interest in nature & the conservation of natural resources
Keywords: Roosevelt, Theodore, 1858-1919--Childhood and youth -- Biography -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Series: Childhood of Famous Americans -- Juvenile literature